Successful Separation of X- and Y-Spermatozoa Ongole Crossbreed Using a Nano-Albumen Gradient Column - T. Maulana; R. Ridwan; M. Gunawan; P. P. Agung; F. Afiati; E. M. Kaiin; S. Said (Faculty of Animal Science, Bogor Agricultural University, 2022)
The objective of this study was to determine the efficacy of separating X- and Y-sperm using nano-albumen (NA). The material used in this study was fresh semen of Ongole Crossbreed bulls with progressive motility of ≥ 70%. Treatments for the top and bottom fractions were T0 (BSA 5% : 10%) as a control, T1 (NA 2% : 4%), T2 (NA 4% : 6%), and T3 (NA 6% : 8%). Sexed semen was evaluated for characteristics and kinematics, and the proportions of sexed semen were validated using morphometric and polymerase chain reaction methods. The data on the characteristics and motility kinematics of X- and Y-sperm were analyzed by ANOVA using Minitab 18. The results revealed that the semen separated by the NA column generally showed the same sperm quality characteristics as the BSA column. However, the total motility of the T3y treatment in the bottom fraction was significantly lower (p<0.05) compared to the control. The kinematics of spermatozoa motility in the top fraction was not significantly different; however, the progressive motility value of T3y was significantly different (p<0.05) compared to that of T1y, and the BCF value of T2y was significantly different from that of the control in the bottom fraction. The acrosome status in the top fraction was better than in the bottom fraction, and the DNA integrity value of the top and bottom fractions showed DNA damage ranging from 2% to 5%. The present study indicated that: (1) the Nano-Albumen gradient column could be used successfully to separate X- and Y-spermatozoa, (2) characteristic values and sperm kinematics, acrosomal status, and DNA integrity were comparable to those of the BSA control, (3) combination column in treatments NA 4% (T2x) and 6% (T2y) appeared the good ability to separated X and Y-sperm.